2019
DOI: 10.3390/cells8060633
|View full text |Cite
|
Sign up to set email alerts
|

Pooling of Patient-Derived Mesenchymal Stromal Cells Reduces Inter-Individual Confounder-Associated Variation without Negative Impact on Cell Viability, Proliferation and Osteogenic Differentiation

Abstract: Patient-derived mesenchymal stromal cells (MSCs) play a key role in bone tissue engineering. Various donor-specific factors were identified causing significant variability in the biological properties of MSCs impairing quality of data and inter-study comparability. These limitations might be overcome by pooling cells of different donors. However, the effects of pooling on osteogenic differentiation, proliferation and vitality remain unknown and have, therefore, been evaluated in this study. MSCs of 10 donors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 45 publications
0
65
0
2
Order By: Relevance
“…Cell line derived from a 15-year-old female Caucasian osteosarcoma patient (Rousseau, Lamoureux et al 2010). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019).…”
Section: U2osmentioning
confidence: 99%
See 4 more Smart Citations
“…Cell line derived from a 15-year-old female Caucasian osteosarcoma patient (Rousseau, Lamoureux et al 2010). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019).…”
Section: U2osmentioning
confidence: 99%
“…However, since primary cells are prone to variance caused by the donor patient (comorbidities, sex, age, etc. ), transferability of study results is limited, thus the donor patients' individual characteristics have to be considered (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019).…”
Section: U2osmentioning
confidence: 99%
See 3 more Smart Citations